Dari Konsep ke Kode: Peningkatan Kompetensi Guru IPA Maros dalam Membuat Media Ajar Digital Arduino Uno - Nurfitra Yanto; Arie Arma Arsyad; St. Mutia Alfiyanti Muhiddin; Shoffan Fatkhulloh; Hasanuddin Hasanuddin (JKM: Jurnal Kemitraan Masyarakat, 2025)
The rapid development of technology requires science teachers to innovate and utilize Arduino Uno as an interactive learning medium to increase student motivation and understanding of abstract concepts. This community service activity aims to improve the professional competence of 24 science teachers in Maros through a three-day hands-on workshop that includes concept socialization, basic programming training, and sensor/actuator assembly. The results showed a significant increase in participants' cognitive understanding of 68.5% (from 42.0 to 71.8), and the creation of 8 functional digital teaching media prototypes from each group (3 participants each). This success proves that practice-based training is effective in empowering teachers to transform science concepts into digital practical tools, thereby independently improving teachers' professional competence in Technology Literacy and Coding Skills and supporting STEM Learning.